Study on analyzing critical challenges faced by LSL: challenges of working in a shipping and logistic company - Kabir, Arvid Asghar (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.